The Use of Artificial Intelligence (AI) in Team Sports - Prediction of Injuries and Optimization of Training - Tsitsagi, Besik (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The paper discusses the possibility of using artificial intelligence (AI) in team sports, in particular its role is focused on the prediction of injuries and optimization of training. The latest trends, such as multimodal data analysis, deep learning algorithms and the integration of wearable devices and relevant technologies, are characterized and analyzed. The paper draws on international experience in football, basketball and rugby, and also discusses ethical and technological challenges. The study highlights the importance of AI for improving athlete health and team performance, especially in the context of Georgian sports.